The Influence of Leadership Style and Organizational Culture on Workplace Well-Being In Company X - Hadiansyah, Widia Karlina; Akbar, Rifqi Farisan (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to investigate the impact of leadership style and organizational culture on workplace well-being among employees at Company X. Workplace well-being refers to an individual's psychological state and overall quality of life within the work environment, influenced by both internal and external factors. Leadership style and organizational culture are considered critical external factors that shape employees' perceptions and work experiences. The study employs a quantitative correlational design with 32 employees as respondents. Data were collected using three instruments: the Workplace Well-being Questionnaire (WWQ), a leadership style scale, and an organizational culture scale. The results of the multiple regression analysis indicate that both leadership style and organizational culture have a significant impact on workplace well-being (p < 0.05). These findings suggest that a positive organizational culture and an effective leadership style are associated with higher levels of employee psychological well-being. The study highlights the importance for organizations to cultivate healthy leadership practices and foster a supportive work environment to promote employee well-being.